Energy‐efficient and sustainable composite facade constructions. Issue 6 (30th December 2021) - Fadai, Alireza; Stephan, Daniel
Abstract : Society currently undergoes a transformation process in understanding the environmental impact of its resource exploitation. The growing importance of resource‐efficiency and the reduction of the environmental impacts are being widely discussed and investigated. Therefore, the European Union (EU) countries have implemented energy efficiency regulations in all sectors, including the building sector, which is accountable for 40 % of energy consumption and 36 % of CO2 emissions within the EU. In modern facade constructions, the use of large‐scaled glass elements is inevitable, which has led to the investigation of potential optimization of structural performance, energy efficiency and ecological characteristics of the structural building components. The Department of Structural Design and Timber Engineering (ITI) at the Vienna University of Technology (TU Wien) developed several timber‐based composite systems, combining timber and wood concrete on the one hand, as well as timber and structural glass components on the other hand. Through various combination of the individual composite systems, certain advantages as well as the synergies resulting from the different combinations could be shown. Different types of combined timber, wood concrete and glass composite structures for facades are developed, assessed and compared to conventional facade structures. The comparison is carried out regarding the materialization on component level, as well as the overall construction level, whereby a scale‐independent assessment of the examined construction types could be reached. This assessment shall further be enabled by a broad‐spectrum computation, ranging from static and dynamic thermal simulations for annual heating and overheating periods up to various thereof resulting ecological impact calculations. In terms of ecological building design, the conceptual implementation of the building envelope plays an important role in the thermal comfort of the inner rooms, as well as the glare and reflection by the use of daylight. One advantage of large‐scale glass facades is the possibility to implement a high portion of solar entries into the total energy concept. The extremely versatile application possibilities allow different sectors of power generation, such as photovoltaic cells in the facade, thermal collectors for heat generation or algae panels, which generate biogas by photosynthesis process. The gained energy can further operate heating and cooling systems but also hot water supply.